Kant and Simmel: aesthetic studies of the thing - Pavlova, Olena (Ukrainian Cultural Studies, 2024)
Background. The thematic and methodological shift accomplished in the critical philosophy of I. Kant is a heritage of world thought and an inexhaustible subject of reflection in the social sciences and humanities. Georg Simmel has repeatedly, both directly (with the reference in the title) and indirectly (by adhering to Kantian principles in his problematics and methodology), engaged with the analysis of the works of the "Copernican revolution" founder. In the small work "The Picture Frame: An Aesthetic Study" one can trace the powerful influence of Kant's aesthetic investigations and the prospects for their rethinking. The study aims to compare the aesthetic studies of the thing by the two great German thinkers in the context of the social sciences and humanities shift in the logic of the Modern discourse crisis.Methods. The methodological basis of the study is a comparative analysis of the guidelines for aesthetic studies of the thing by I. Kant and G. Simmel. The optics of modern humanities, in particular the further movement of humanitarian thought towards "criticism of the abstraction of aesthetic consciousness" (H. Gadamer) and the grounding of the ontological status of a work of art, as well as its origins and further prospects of cultural history, allow us to highlight the "liquefaction of Modernity" (Z. Bauman), in particular in the shift of the subject fields of the social sciences and humanities.Results. Based on Kantian approaches to substantiating the "autonomy of the art world", one can trace the peculiarity of Simmel's understanding of the specificity of how a work of art functions in comparison to a natural phenomenon. The requirements for the appearance of a work of art as a special form of the thing extend to its surroundings, particularly the frame of the painting. Simmel formulates in detail the requirements for the order of the painting frame signifiers.Conclusions. The comparative analysis of the aesthetic studies of the thing by I. Kant and G. Simmel reveals the unity of their initial themes and methodological guidelines, as well as the shift in their approaches in the context of the crisis of the discourse of Modernity. The latter is manifested in the difference between the recognition of the substantial status of the thing in philosophy and the instrumental foundations of the sociological approach. The methodological guidelines of cultural inquiries become clearer in this fundamental shift.
Keywords: I. Kant; G. Simmel; aesthetic study; thing-in-itself; thing; work of art; picture frame